Graphical Password Schemes Design: Enhancing Memorability Features Using Autobiographical Memories. - Obasan Adebola; Norafida Ithnin; Nicholas Akosu; Mohd Zalisham Jali (Asian Research Publishing Network (ARPN), 2024)
Memorability and security of passwords are two distinct extremes that are difficult to achieve at the same time. These two important features are a major problem in conventional textual password systems. Text-based is a system where memorability is inversely proportional to security of passwords as such users choose weak texts as passwords to make it easy for themselves to remember at the expense of security. A weak password is easy to remember but provide little or no security because weak password is easy to break. To correct this flaw , graphical passwords are developed as an alternative to text-based passwords. However, a number of existing graphical schemes still have some drawbacks. The present study introduces a framework of a graphical password scheme using autobiographical memories to improve the memorabily of passwords. With this feature, user can write or draw two characters in each round of the grid cells for three rounds during the password creation and later use the corresponding cells in three rounds for authentication, without touching the grid system in order to prevent the password from being seen by any nearby observer and ultimately to resist against shoulder surfing